DEVELOPMENT OF LAWS ON ISLAMIC FINANCE IN THE LEGISLATION OF UZBEKISTAN (American Journal of Technology and Applied Sciences, 2025)
The article discusses the legal framework for organizing and coordinating the activities of Islamic finance organizations in Uzbekistan, the content and essence of regulatory legal documents adopted in the field of Islamic finance, and the processes of their implementation in practice.